The Implementation of Problem-Based Learning (PBL) Model to Improve Students’ Critical Thinking Skills in Civics Subjects - Fathurrohman, Fathurrohman; Suparlan, Suparlan; Nurohmah, Lutfiana; Nurhayati, Nurhayati (Jurnal Prima Edukasia, 2025)
This study aims to enhance students’ critical thinking skills through the implementation of the Problem-Based Learning (PBL) model in Pancasila Education, which is designed to foster analytical, evaluative, and problem-solving abilities systematically. The research employed a Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model. The subjects consisted of 16 fourth-grade students from Bangirejo I Elementary School. Data were collected through observation, critical thinking skill tests, and documentation. The data were analyzed using both qualitative descriptive and quantitative descriptive techniques. The findings reveal that: (1) based on observations, students’ critical thinking skills showed significant improvement, with mastery learning increasing from 31% in the first cycle to 81% in the second cycle; and (2) the results reinforce the effectiveness of the PBL model in enhancing elementary students' critical thinking abilities. Moreover, the study contributes to the development of active learning strategies aligned with the demands of 21st-century education, particularly in the context of Pancasila Education.